2018
DOI: 10.11622/smedj.2017043
|View full text |Cite
|
Sign up to set email alerts
|

Venous ultrasonography findings and clinical correlations in 104 Thai patients with chronic venous insufficiency of the legs

Abstract: Calf vein reflux plays an important role in CVI and in patients with recurrent ulceration after previous superficial venous surgery. Although GSVR was present in most patients with CVI in the legs, SSVR may present in one-third of patients, especially those with lateral ulceration. The high prevalence of DVR in the absence of DVT and the presence of a pulsatile venous signal in some patients highlight the incomplete understanding of CVI aetiology.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
9
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 18 publications
(23 reference statements)
1
9
0
Order By: Relevance
“…Kanchanabat et al also supported the same findings, noting CVI to be more prevalent among females (54.4%). 8 ) However, the findings of the study conducted by Khan et al proved otherwise, demonstrating that CVI was more prevalent in males (52.6%) compared to females (47.4%). The difference may be due to different selection criteria and different population studied (hospital vs. community).…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…Kanchanabat et al also supported the same findings, noting CVI to be more prevalent among females (54.4%). 8 ) However, the findings of the study conducted by Khan et al proved otherwise, demonstrating that CVI was more prevalent in males (52.6%) compared to females (47.4%). The difference may be due to different selection criteria and different population studied (hospital vs. community).…”
Section: Discussionmentioning
confidence: 88%
“…Univariate analysis factors associated with severity of disease (n=121) Significant also noted that CVI was common among female patients in a study they have conducted on hospital patients. Kanchanabat et al also supported the same findings, noting CVI to be more prevalent among females (54.4%) 8). However, the findings of the study conducted by Khan et al proved otherwise, demonstrating that CVI was more prevalent in males (52.6%) compared to females (47.4%).…”
mentioning
confidence: 75%
“…This is probably due to the fact that SSV insufficiency is rarer. 20 Failure to remove all varicosities was compensated as PI for the operations carried out in 2003 and 2005. It is possible that more recent decisions would not consider patient’s experienced insufficient removal of side branches as a compensable injury as treatment of the truncal disease is, nowadays, considered the main focus of the approach.…”
Section: Discussionmentioning
confidence: 99%
“…33 Primary DVI has been well documented and may account for an unknown percentage of reflux in the deep vein system. Kanchanabat and Stapanavatr recently reported that, in DVT-negative patients, there is still a non-negligible incidence of deep venous reflux, 34 but insufficiency of deep veins in DVT-negative patients is not a new finding. In 1995, Caps et al detected the presence of a post-DVT valve insufficiency even in veins not involved primarily in the thrombotic process.…”
Section: Veins Insufficiency In Dvt-negative Limbs Without Ulcermentioning
confidence: 99%